Humor Styles in Marriage: How Similar Are Husband and Wife?. Issue 6 (December 2019) - Tsai, Meng-Ning; Wu, Ching-Lin; Chang, Yu-Lin; Chen, Hsueh-Chih
Past research found that similar appreciation for humor exists between spouses, but it is not certain whether this similarity between spouses also exists in kindhearted or malicious humor. The present study investigated the similarity of Taiwanese married couples' humor styles. Participants included 239 couples (mean age = 42.9 years) who had been married to each other for at least 10 years. We used a traditional Chinese edition of the Humor Styles Questionnaire to measure the humor style and clustered participants' humor styles in order to examine the similarity between spouses. The results show that husbands have higher tendencies toward aggressive (Cohen's d  = 0.29, p  < .01) and self-defeating (Cohen's d  = 0.35, p  < .01) humor styles than wives. Results from multilevel modeling indicate that spouses' aggressive ( p  < .001, confidence interval = .17, .41) and self-defeating ( p  < .01, confidence interval = .05, .30) humor styles acting as a valid predictor to the other spouses' negative humor styles. Furthermore, the results show that personal humor styles could be categorized into four clusters: positive humor endorsers, negative humor endorsers, general humor endorsers, and humor deniers. According to the clusters within spouse pairs, results show that similarities in humor styles exist between spouses (χ 2  = 16.73, p  = .01). The current study finds that most couples have similar humor styles and that a high proportion of married couples share the same humor clusters.